Nonlocal theoretical analysis of the dynamic behavior of two Griffith cracks in a piezoelectric strip (Archives of Mechanics - Test, 2004)
The dynamic behavior of two Griffith cracks in a strip made of piezoelectric materials under anti-plane shear waves is investigated by means of the non-local theory for impermeable crack surface conditions. A one-dimensional non-local kernel is used instead of a two-dimensional one for the anti-plane dynamic problem to obtain the stress and the electric displacement near the crack tips. By utilizing the Fourier transform, the problem can be solved by means of two pairs of triple integral equations. These equations are solved using the Schmidt method. Contrary to the classical solution, it is found that no stress and electric displacement singularity are present at the crack tip. This is shown to be consistent with the physical nature.